Pelatihan Seni Tari di Sanggar Seni Banaspatiraja untuk Meningkan Keterampilan Menari Anggota Sanggar - Jeni, Jeni; Renda, Rapi (CV. Global Cendekia Inti, 2025)
The service article with the title Dance Training at Banaspatiraja Art Studio to Improve Dance Skills of Studio Members is motivated by the researcher's awareness in improving the quality of dance performance art in East Lombok. So far, the arts ecosystem in East Lombok has only experienced very rapid development but the problem is the lack of actors who are consistent in making dance performance concepts which results in the cessation of regeneration or successors. The purpose of this training is to produce choreographers who not only understand the art of dance practically but also choreographers who are able to create dance concepts accompanied by good dance skills and understand the meaning and values in making a dance. The training was held at Sanggar Banaspatiraja in Masbagik. The method used in the training was the demonstration method combined with hands-on practice and reflective discussion. The results of the training found the emergence of new choreographers from the studio who understand dance both in theoretical and practical perspectives in terms of dance skills. These choreographers then become the successors in maintaining the existence of Banaspatiraja studio.